Financial Knowledge, Socialization, and MSME Financial Management Behavior: Evidence from a Perceived Behavioral Control Perspective - Siska Putri Utami; Yusron Toto (Institut Bisnis dan Ekonomi Indonesia, 2026)
This study examines the determinants of financial management behavior among micro, small, and medium enterprises (MSMEs) by integrating Behavioral Finance Theory and the Theory of Planned Behavior. Specifically, it investigates the roles of financial knowledge and financial socialization, with perceived behavioral control as a mediating variable. Using a quantitative approach, data were collected through a structured questionnaire from 160 MSME owners in Pontianak City, Indonesia. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that financial knowledge does not directly influence financial management behavior but significantly enhances perceived behavioral control. In contrast, financial socialization has both direct and indirect effects on financial management behavior. Perceived behavioral control is found to significantly influence financial management behavior and fully mediates the relationship between financial knowledge and financial management behavior, while partially mediating the relationship between financial socialization and financial management behavior. These results suggest that cognitive financial knowledge alone is insufficient to drive effective financial behavior unless individuals perceive adequate control over financial decisions. This study contributes to the behavioral finance literature by highlighting perceived behavioral control as a key psychological mechanism in shaping MSME financial behavior. The findings provide practical implications for policymakers and practitioners to design financial empowerment programs that emphasize behavioral control and social learning alongside financial literacy.